Pendampingan Pengelolaan Media Sosial Sebagai Optimalisasi Branding Sekolah - Tijow, Meylani Aljeinie; Risamasu, Putri Ellen Gracia; Patappa, Maghfira Maulani; Sembiring, Desy Anita Karolina; Sogalrey, Febi Adriana Mutiara; Pekey, Cerry Hanna Grace; Simanjuntak, Grace Marsaulina (Carmin: Journal of Community Service, 2024)
In today's digital era, social media has become an important communication tool for educational institutions to build and strengthen the school's image. The purpose of this service is to help one of the public high schools in Jayapura City optimise the use of social media for their branding. The school was newly inaugurated in 2024 as a result of the merger of two schools. The method used in this assistance is the classical method, where the service team consisting of students of the Education Management Study Programme assists the school's social media team, with the output target being an active and attractive school social media. The results of the service showed an increase in social media management skills and optimisation of school branding and communication. In addition, the community's response to the existence of school social media is very positive, where in a short period of time the number of followers, viewers and likes on school social media has increased.